A Review on Role of Music in Premature Infants Mentioned in Charaka Samhita - Choudhary, Payal; Roman, Sheetal (International Research Journal of Ayurveda & Yoga, 2023)
Music therapy has been in use since ages in healing various ailments across the globe. As an evidence-based, allied health-care profession, it is flourishing in western world where various programs, bachelor degrees, and foundations are being laid down. In India, music has got its roots from Samaveda where it is being mentioned to be used for various purposes. In Ayurveda, it is described as a Vajikaraka (aphrodisiacs), as a pitta Dosha pacifier, as a protective measure for new born, for Nidranasha (insomnia) treatment, etc. More detailed or evidence-based study should be done on how does the music effect the individual in these conditions. In this article, a possible view on role of music in premature infants is explained. We can use the results extracted to promote health in this form. As evidence-based study has more importance in today’s world so there is a need to validate old facts with recent researches.